Discursive strategy on UFM on YouTube. Construction of a hate speech. - Gil-Ramírez, Marta; Gómez-de-Travesedo-Rojas, Ruth (Historia de los Sistemas Informativos, 2022)
Introduction: In the last year the migratory phenomenon related to Unaccompanied Foreign Minors (hereinafter UFM) has obtained a special media coverage in the Spanish context, motivated, among other issues, by the negative publicity towards this group that the far-right party Vox has used during the campaign for the Madrid elections of 2021. In the absence of previous literature, this research aims to determine the representation that, on YouTube, is constructed and transmitted about the UFM. Methodology: An exploratory-descriptive study is proposed, in which content analysis and critical discourse analysis are used to examine the most popular videos, in the proposed social network, under the UFM-Spain label. Results: A characterization of the UFM prevails based on subjectivity, the use of a pejorative, denigrating and incriminating language that revolves around the association of these minors with the concept of threat. Discussion: The findings are consistent with previous research that analyzes the migratory phenomenon as a whole, but it represents a novelty in terms of the analysis of the specific typology of migrants that constitute the UFM, whose representation through social networks has not yet been explored at the academic level. Conclusions: The content posted on this social network contributes to spreading hate speech towards the UFM, mainly on the basis of oversizing the conflict and homogenizing the collective around negative attributes.
Keywords: Discurso del odio - En los medios de comunicación social; Menores emigrantes - En los medios de comunicación social; UFM; YouTube; VOX; Immigration; Social networks; Hate speech